Clara Schumann : piano virtuoso - Reich, Susanna (New York : Clarion Books, 1999)
Describes the life of the German pianist and composer who made her professional debut at age nine and who devoted her life to music and to her family.
Includes index.
Keywords: Schumann, Clara, -- 1819-1896 -- Juvenile literature; Schumann, Clara, -- 1819-1896.; Pianists -- Germany -- Biography -- Juvenile literature; Pianists; Women -- Biography